2021
DOI: 10.1021/acs.jpclett.1c02019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Initial Hydrogen Spillover from a Single Atom Platinum Active Site to the Cu(111) Host Surface: The Impact of Substrate Electron–Hole Pairs

Abstract: The initial impulsive diffusion of hot hydrogen atoms resulted from the dissociative chemisorption of H 2 at atomically dispersed Pt atoms embedded in Cu( 111) is investigated using ab initio molecular dynamics. Upon dissociation, one of the two hydrogen atoms tends to roam away from the dissociation site while the other remains trapped. It is shown that the fraction of diffusion and the average diffusion length increase with the incident energy and H 2 vibrational excitation, due apparently to the increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 63 publications
9
36
0
Order By: Relevance
“…As expected, there are clearly two regions: one corresponding to the initial impulsive diffusion of the hot H* atoms ( t < 5 ps) and the other suggestive of conventional diffusion of a thermal H* atom at a longer time scale ( t > 20 ps). As expected, the former ballistic diffusion depends sensitively on the initial condition, such as the incidence energy and angle, as shown in our earlier publication . However, the latter self-diffusion has essentially an unchanged diffusion behavior for different initial conditions, also shown in Figure S3 in the Supporting Information.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…As expected, there are clearly two regions: one corresponding to the initial impulsive diffusion of the hot H* atoms ( t < 5 ps) and the other suggestive of conventional diffusion of a thermal H* atom at a longer time scale ( t > 20 ps). As expected, the former ballistic diffusion depends sensitively on the initial condition, such as the incidence energy and angle, as shown in our earlier publication . However, the latter self-diffusion has essentially an unchanged diffusion behavior for different initial conditions, also shown in Figure S3 in the Supporting Information.…”
Section: Resultssupporting
confidence: 84%
“…Following the dissociation at the Pt site, we observed that one hydrogen typically undergoes facile hopping from the Pt site to Cu sites with increasing distances, similar to the behavior observed in the earlier theoretical work on Pd/Cu(111) by Busnengo and co-workers . However, our study suggested that the characteristic diffusion time and length of the adsorbed H* atom are strongly influenced by the interaction with the surface electron–hole pairs (EHPs) . The resulting electronic friction (EF) slows the spillover significantly, underscoring the importance of nonadiabatic effects. Indeed, the importance of electronically nonadiabatic dissipation in H* diffusion in metals has been noticed before using model potentials. , More recently, nonadiabatic energy dissipation of H atoms in scattering from metal surfaces was observed experimentally and characterized theoretically. , Theoretical predictions of nonadiabatic energy dissipation for hot H* atoms on various metal surfaces have also been made by several groups. …”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations